Point defects and diffusion in oxides - Shi, J.; Becker, K. - D. (Видавництво Львівської політехніки, 2012)
Electronic and ionic defects are unavoidable elements of structural disorder in oxide materials resulting from nonstoichiometry or impurity/doping ions. Many point defects involving electrons or transition metal ions give rise to optical absorption, providing a probe to study defect chemistry and transport properties in these materials. We present the application of optical in-situ spectroscopy to the investigation of defects and defect-related processes at elevated temperatures in N-doped titania films and Lideficient lithium niobate.
Keywords: point defects; diffusion; optical spectroscopy; N-doped TiO2-d thin film; lithium niobate